2012
DOI: 10.1007/s00403-012-1215-7
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-dependent and Nrf2-independent induction of phase 2 detoxifying and antioxidant enzymes during keratinocyte differentiation

Abstract: As antioxidant enzymes can be actively modulated during keratinocyte (KC) differentiation, this study was aimed to evaluate the modulation of a group of phase 2 detoxifying and antioxidant enzymes (phase 2 enzymes) during KC differentiation. In postconfluence-induced differentiation model of KC, heme oxygenase-1 (HO-1), NADP(H):quinone oxidoreductase-1 (NQO-1), and glutathione S-transferase pi (GSTpi) were up-regulated at a transcriptional level. In Western blot analysis, the phase 2 enzymes were up-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…23, 24 We further demonstrate that transcriptional regulation of HO-1 expression occurs via an NRF2-independent manner similar to human keratinocytes. 25 Although HO-1 overexpression in BeWo choriocarcinoma cells increased tumor cell adhesion and expression of PXDN, 26 we did not observe marked changes in PXDN or adhesion function with HO-1 overexpression in T80 cells.…”
Section: Discussionmentioning
confidence: 56%
“…23, 24 We further demonstrate that transcriptional regulation of HO-1 expression occurs via an NRF2-independent manner similar to human keratinocytes. 25 Although HO-1 overexpression in BeWo choriocarcinoma cells increased tumor cell adhesion and expression of PXDN, 26 we did not observe marked changes in PXDN or adhesion function with HO-1 overexpression in T80 cells.…”
Section: Discussionmentioning
confidence: 56%
“…Unlike HO-1, in our results, expression of NQO1 upregulated by oleanolic acid was more prominent on day 7 than on day 3. There appears to be some differences in the expression of phase 2 enzymes according to the experimental model: the regulatory mechanisms of phase 2 enzymes in relation to the Nrf2 pathway may be tissue- or cell-specific [28]. Our results suggest that HO-1, rather than NQO1, plays a major role in the attenuation of renal inflammation and fibrosis in this UUO model.…”
Section: Discussionmentioning
confidence: 79%
“…Similar modulation of these phase II enzymes was observed during keratinocyte differentiation as well. 34 These results suggested that other mechanisms besides Nrf2 pathway might be involved in the induction of the antioxidant genes in this ALS mouse model. Indeed, previous study showing the induction of HO-1 in Nrf2-deficient MEF and HEK-293 cells provided evidence that HO-1 can be regulated by Nrf2-independent mechanisms.…”
Section: Effect Of Nrf2 Knockout On Als Mice Y Guo Et Almentioning
confidence: 73%